Levels of concentrate and sources of non-fiber carbohydrates on productive performance and ruminal kinetics of finishing cattle - Ferrari, Viviane Borba (2017)
The objective of this study was to quantify the effect of partial replacement of finely ground corn by steam-flaked corn or pelleted citrus pulp and two concentrate levels, either 60 or 80%, on rumen pH, in vitro digestibilities of tropical forages, performance and rumen fermentation of Nellore young bulls. Three rumen cannulated Nellore steers with average BW of 350 ± 15 kg were assigned in a 3×3 Latin Square design. The rumen pH was measured and rumen fluid used to evaluate in vitro DM and NDF digestibilities (IVDMD and IVNDFD) of tropical forages. Moreover, a total of 108 Nellore young bulls with initial BW of 365.3 ± 3.12 kg, were distributed in collective pens, with 3 animals per pen, in a randomized complete block design with 6 replicates in a 3×2 factorial arrangement of treatments. The performance, carcass traits, blood parameters, feeding behavior, and sorting index were evaluated. Additionally, six rumen-cannulated steers, weighing 345.10 ± 14 kg were arranged in 2 6×6 non-contemporary Latin squares, in a 3×2 factorial arrangement of treatments. The rumen was manually evacuated, an aliquot of the digesta was filtered to separate solid and liquid phases. Rumen fluid samples were taken at multiple times after feeding to determine pH, short chain fatty acids and ammonia nitrogen. The steam-flaked corn decreased in vitro digestibility of the forages evaluated, but increased rate of degradation. It also increased propionic acid, but decreased ammonia compared to the other diets. It decreased NDF total tract digestibility compared to citrus pulp. The steam-flaked corn increased fat deposition, with no impact on animal performance. The citrus pulp decreased lag time and increased rate of degradation. The pelleted citrus pulp caused the bulls to sort the diet against large particles, decreasing the DMI, performance, and rumen propionic acid concentration, but increased the acetic acid, disappearance rate of NDFd, and digestibilities of DM and OM. On the other hand, the 80% concentrate diets decreased passage rate of NDF, but increased the digestibilities of OM, DM, and performance, despite the lower intake. In conclusion, the inclusion of 80% concentrate in sugarcane silage based-diets lowers intake, and increases performance, the partial replacement of ground corn by steam-flaked corn improves carcass fat deposition. And citrus pulp increases rumen pH, fiber digestibility but decreases intake, and performance of finishing young Nellore bulls.